Genetic polymorphisms of CXCL8 (-251) are associated with the susceptibility of helicobacter pylori infection increased the risk of inflammation and gastric cancer in Thai gastroduodenal patients - Wongwarut Boonyanugomol (2020)
© August 2019, Iran J Allergy Asthma Immunol. CXC Chemokine Ligand 8 (CXCL8) plays an important role in gastric inflammation and in the progression of gastric cancer induced by Helicobacter pylori (H. pylori) infection. The association of CXCL8, CXC Chemokine Receptor 1 (CXCR1), and CXC Chemokine Receptor 2 (CXCR2) polymorphisms with H. pylori infection and gastric cancer progression needs to be investigated in a population within an enigma area consisting of multiple ethnicities, such as Thailand. To analyze the relative risk of H. pylori infection and gastric cancer among Thai gastroduodenal patients, gene polymorphisms in CXCL8 (promoter region -251) and in CXCR1 and CXCR2 (receptors for CXCL8) were detected by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and allele specific-PCR (AS-PCR). We also determined the presence of cytotoxin-associated gene A (cagA) in Thai patients with H. pylori infection. Correlation between the CXCL8 (-251) polymorphism and CXCL8 gene expression was evaluated by quantitative reverse transcriptase-PCR (qRT-PCR). We found a significant association between the T/A and A/A genotypes of CXCL8 (-251) with H. pylori infection. However, no significant correlation was found between the CXCR1 (+2607) and CXCR2 (+1208) gene polymorphisms with H. pylori infection among Thai gastroduodenal subjects. Within the H. pylori-infected group of Thai gastroduodenal patients, no significant differences in cagA were observed. In addition, the A/A genotype of CXCL8 (-251) significantly correlated with the risk of gastric cancer and correlated with higher CXCL8 gene expression levels in Thai gastroduodenal patients. These results suggest that CXCL8 (-251) polymorphisms are associated with H. pylori infection, an increased risk of stronger inflammatory responses, and gastric cancer in Thai gastroduodenal patients.